‘A Lighthouse on the Beach’ Stories, Metaphors, and Anecdotes in Teachers’ Personal Recounts - Selim Ben Said (Universitat Autònoma de Barcelona, 2013)
Recent interest in teacher identity in general and language teachers’ identity in particular has shown that although identity research can be contentious, its examination can cast light on the process of teacher development. In fact, the role of identity in teacher development has been promoted as a key analytical framework. In this study exploring narratives elicited from interview data, I examine how a novice teacher develops more confidence in her role(s) as a teacher by recounting stories based both on her imagined identity as a teacher but also on her practical experience in the classroom. Along with the stories shared by the teacher, she intuitively reflects on her professional identity through the use of metaphors and anecdotes. These under-researched aspects of narrative inquiry are presented in the paper as symbolic discursive proxies that the teacher uses to carve out a space of self-definition within the teacher community of practice.